2021
DOI: 10.1111/ajae.12212
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Agriculture in the Economy: Impacts from COVID‐19

Abstract: Much of the attention from COVID‐19 has been on the impacts on tourism and other service sectors; but there has been a growing interest in some agricultural and food topics, such as the decline in food away from home (FAFH) expenditures. Our work considers the importance of FAFH in the overall economy, and we also consider changes in agricultural production and trade that have occurred because of COVID‐19. We gather data on actual changes to these components, as well as similar shocks to non‐agricultural secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 30 publications
4
66
0
1
Order By: Relevance
“…In other countries, too, monitoring capacities and legal enforcement of measures to reduce tropical deforestation have been reduced due to budget restrictions of environmental agencies or impairments to ground-based monitoring that prevents land grabs and tenure conflicts (Brancalion et al, 2020, Amador-Jiménez et al, 2020. Effects of the pandemic on trends in fire activity or forest cover changes are hard to separate from those of general political developments and environmental changes and the long-term consequences of disruptions in agricultural and forestry economic activities (e.g., Gruère and Brooks, 2020;Golar et al, 2020;Beckman and Countryman, 2021) remain to be seen.…”
Section: Final Year 2020mentioning
confidence: 99%
“…In other countries, too, monitoring capacities and legal enforcement of measures to reduce tropical deforestation have been reduced due to budget restrictions of environmental agencies or impairments to ground-based monitoring that prevents land grabs and tenure conflicts (Brancalion et al, 2020, Amador-Jiménez et al, 2020. Effects of the pandemic on trends in fire activity or forest cover changes are hard to separate from those of general political developments and environmental changes and the long-term consequences of disruptions in agricultural and forestry economic activities (e.g., Gruère and Brooks, 2020;Golar et al, 2020;Beckman and Countryman, 2021) remain to be seen.…”
Section: Final Year 2020mentioning
confidence: 99%
“…Kejzar and Velic (2020) characterize the impacts of COVID-19 on supply chains in terms of the relative upstream or downstream position of an industry. Recently, Beckman and Countryman (2021) found that agricultural trade increased by 2.3 percent in 2020; but the information they present is at a highly aggregated level—and only accounts for total 2020 trade, without providing the decomposition done here. Arita, Grant and Sydow (2021) provided a preliminary “early look” assessment of the impacts on agricultural trade using quarterly country-level data on imports of agricultural and non-agricultural commodities in a non-directional framework using data through August 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified key elements of the effects of the coronavirus pandemic on food demand/security and calorie intake (FAO, 2021;Laborde et al, 2021;O'Connell et al, 2021) as well as the broader implications of pandemic-induced food expenditure shocks on GDP (Beckman and Countryman, 2021). We show the potential of our approach to contribute to this research with some illustrative food demand projections.…”
Section: Food and Covid-19mentioning
confidence: 87%